Le pouvoir des étoffes, la Grande Fabrique de Lyon au service de l’Empire - Aziza Gril-Mariotte (Bulletin du Centre de Recherche du Château de Versailles)
The silks produced by Lyon’s manufacturers for the imperial palaces featured new ornamental motifs, often influenced by the artistic grammar developed by Percier and Fontaine. Lyonnais designers, in response to commissions from the Garde-Meuble Impérial, subscribed to this vocabulary, which contributed to the magnificence desired by the Emperor for the advent of a new political order. The study of a corpus of some ten textile pieces, including some commissioned for the refurnishing of the Palace of Versailles at the time of Napoleon’s second marriage, which was a founding moment for the Empire, allows us to examine the motifs of the fabrics according to their destination in the imperial residences. Lyonnais manufacturers responded to the precise demands of the Garde-Meuble Impérial, respecting the symbols of power for certain fabrics, but the designers also drew on pictorial tradition dating back to the eighteenth century. This article examines the sources of inspiration and models used in the silks to show how certain emblematic pieces played a part in the display of power, while the vast majority of hangings and borders produced in Lyon combined antique forms and floral models, contributing to the artistic blossoming of the nineteenth century.